Perception of Ease, Trust, and Payment Risk on Interest in Using the Gopay E-Wallet Among Economics Education Students at Sebelas Maret University, Surakarta - Sheila Desita Mahardani; Harini Harini (Cahaya Abadi Publisher, 2026)
This research aims to analyze the influence of perceived ease of use, trust, and payment risk on the intention to use the GoPay e-wallet among Economics Education students at Universitas Sebelas Maret Surakarta. The background of this research is based on the increasing use of e-wallets among students and the importance of psychological and security factors in the adoption of digital financial technologies. This study employed a quantitative approach with a survey method using questionnaires distributed to 193 respondents selected through purposive sampling. Data analysis was conducted using multiple linear regression with the help of SPSS 26 software. The results showed that partially, perceived ease of use and trust have a positive and significant effect on the intention to use GoPay. On the other hand, perceived risk has a negative but significant effect. Simultaneously, all three independent variables have a significant influence on the intention to use GoPay. These findings support the Technology Acceptance Model (TAM) and Fintech (Finansial Technology), which suggests that ease of use are key determinants of technology acceptance, while perceived risk can serve as a psychological barrier reducing user intention. The study provides important implications for e-wallet service providers to enhance ease of use and security features in order to build trust and reduce users’ perceived risks, especially among university students.